Strategi Penanggulangan Stres Pada Social Worker Dengan Menggunakan Brain Respiration - Efnie Indrianie (Universitas Kristen Maranatha, 2023)
This study aims to determine how effectively Brain Respiration reduces stress levels in social workers. This study uses the Quasi-Experimental method and purposive sampling as the sampling technique. 30 social workers participated in this study. 15 participants became experimental group participants, and 15 others became control group participants. Biofeedback tools were used to measure the degree of stress through electrodermal activity (EDA). The analysis used was Wilcoxon and Mann-Whitney nonparametric statistics. The analysis showed a difference in the degree of stress, namely a decrease in the degree of stress in social workers in the experimental group after using Brain Respiration (T-count = 6 and T-table = 25). Brain Respiration can reduce stress in social workers when comparing the degree of stress of the experimental and control groups (U-count = -34.5, and U-table = 70). The conclusion is that Brain Respiration can minimize the degree of stress in social workers.